Domes Restoration Process Technique - Mohd Nazri, Nur Farrahain; Mohamad, Mimi Mohaffyza (Research and Innovation in Technical and Vocational Education and Training, 2023)
A general objective of structural design that aims to provide protection is unrestricted free space. The potential structure, expense of materials, and difficulty of building limit the necessity for such a facility. This objective can be effectively achieved using space structure and more specifically, the dome structure system. The dome's ability to be formed so that its members are below the pressure axis is a benefit. Metal alloys like steel and aluminum, which have a relatively good strength-to-weight ratio, are the most popular building materials for long-span domes. This technique tries to locate appropriate tools and supplies for the task of recoating dome panels that have coating issues with the current technique. The court complex served as the site for this study, which involved an experiment representative from the applicator and specialist as well as the contractor and client, who carried out 4 experiments with various tools and materials to determine their suitability for the work process. Based on the study's findings, it was discovered that one of the materials and pieces of equipment that had been tested had produced a result that could be agreed upon by all parties, specifically the use of grinder points that were suitable for the client-required criteria. It is also because it saves time taken.